(untitled) (Journal of Tikapur Multiple Campus, 2015)
Government of Nepal adopts this system since Nov. 16, 1997. After several year planning and preparation, VAT act was finally passed through parliament in December 1995. VAT became effective through the finance bill of 1997. VAT avoids the another tax such as sales tax, entertainment tax, hotel tax and contract tax, Nepal was introduced consumption types of VAT, base on the destination principle with single positive rate of thirteen percent. Nepal is a developing county; resource mobilization is one of the alternatives to develop. VAT is necessary to introduce for revenue collection, promote economic growth, for improving deteriorating macro economic performance, to establish an account based modern transparent tax system, to make the tax system more scientific, to get the confidence of donor, to make Nepalese tax system effective. Source of VAT revenue in Nepal are domestic VAT and imports VAT. Share of import VAT revenue is two third and share of domestic is one-third in total VAT revenue. It is expected that the share of import and domestic VAT revenue may be equal in near future. Source of domestic VAT revenue are production, distribution and service sectors. Since value added tax (VAT) has recent approach, it has also much potentiality power to generate revenue than earlier sales tax because it covers broad coverage and all level of production, distribution and sales. Revenue is the crucial element for the government to accomplish operating and development activities. Tax is the major source of revenue. It contributes a significant share in total tax revenue and total revenue but a little share in GDP in Nepalese context. Revenue mobilization is one of the major concerns for Nepal.